Evaluation of Information Security Readiness Level Using the Integration of KAMI Index 5.0 and ISO/IEC 27001:2022 - Nasya Ananda Rozi; Agus Wijayanto; Wahyu Nur Alimyaningtias (Journal of Applied Informatics and Computing, 2026)
Information security is a strategic aspect that determines the continuity of organizational operations amid an increasing dependence on digital systems. PT. QAZ, as a regionally owned business entity providing clean water services, relies on information systems to support customer management, payment systems, and distribution network management, so evaluating the readiness of its information security is crucial. This study aims to measure the level of information security readiness of PT. QAZ through the integration of the KAMI Index 5.0 with ISO/IEC 27001:2022 control using a mixed methods approach. The results of the evaluation of the Electronic Systems Category obtained a score of 19 points with a high category, while the accumulation of the sixth score in the evaluation area reached 372 out of a maximum total of 918 points, with the achievement of the supplement category of 26%. In detail, the maturity level of each domain is: Level I+ Information Security Governance, Level II Risk Management, Level I Information Security Management Framework, Level I+ Information Asset Management, Level II Information Technology and Security, and Level I Personal Data Protection.